Crossmatch to Transfusion Ratio (C/T Ratio) Komponen Darah WB dan PRC - Safitri, Valina Intan; Negoro, M. Syamsul Arif Setiyo (Jaringan Laboratorium Medis, 2023)
A crossmatch test between patient and donor’s blood must be carried out before blood transfusion. However, not all crossmatched blood will be transfused to the patient. This indicates inappropriate distribution of blood products, blood wastage, inaccessibility of blood for emergency patients, increased costs, and increased workload for staff. Crossmatch to Transfusion Ratio (C/T Ratio) is used as an indicator to determine the efficiency of blood use and can serve as a guide to anticipate excessive blood demand. This study aims to determine C/T Ratio score of blood components WB and PRC in the Brebes Regency Hospital 2021. This research is a descriptive study with a retrospective approach. Sampling was done using total sampling technique. Data was obtained from the blood requests recapitulation book in Brebes Regency Hospital’s Blood Bank 2021. The result showed there were 47 units WB crossmatched and 34 units (72%) transfused. There were 4589 units PRC crossmatched and 4369 units (95%) transfused. The C/T Ratio score of WB is 1.38. The C/T Ratio score of PRC is 1.05. The overall C/T Ratio score is 1.05.